The Effects Moving Up And Down The Bench At Night For 20 Minutes On Decrease Blood Sugar Levels - Ahmad Syauqi Al Fanjari; Samsul Bahri; Yasep Setiakarnawijaya; Muhamad Ilham (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2023)
This study aims to determine the effect of work up and down the bench at night. Subjects in this study are students of SMAN 12 Tangerang totaling 25 people, clinical trial research with research design “One Group Pre-test and Post-test Design”. The measured Parameter is the blood glucose level. The results obtained pre-test and post-test glucose levels after doing activities up and down the bench. The data analysis technique used is the T-test technique (t-test) by calculating the value of t-count compared to the T-table at degrees of freedom n-1 and at the level of significance (p<0.05). From the results of research on the activity of the effects of work up and down the bench at night for 20 minutes, obtained the average value of pre-test blood sugar levels is 114.8 and the average post-test is 97.6 the value of the difference between pre-test and post-test is 17.2. Conclusion activity up and down the bench at night for 20 minutes affects a significant decrease in blood sugar levels and is easy to do.